Yakuwarigo Used in “Nagasarete Airantou” Manga - Rahardjo, Hardianto (CENTRAL ASIA AND THE CAUCASUS, 2022)
The use of Yakuwarigo, a term created by Kinsui Satoshi to describe a “virtual Japanese language” used in fictional works to accentuate certain character’s personality, gender, age or even birthplaces through the way they speak. This article is written in a descriptive analysis manner to provide one among many examples on the importance of Yakuwarigo in a story that consists of many characters, each with their own names, backgrounds, personalities and role in the big story. The data of this article are characters, or specifically their way they are talking, which indicates the use of yakuwarigo and an example of linguistic stereotypes being used in a manga titled “Nagasarete Airantou” written by Fujishiro Takeshi. The story is about a boy whose ships he is on is sunken and h got stranded on a secluded island filled completely with female residents. Many of the female characters are the descendants of many survivors who got stranded on the island as well from various places in Japan and other countries. Some of the “heroines” speaks in each of their own distinctive styles, which will be identified as a Yakuwarigo or not and whether this has any connections to their backgrounds and stereotypical personalities.